Improving Students’ Vocabulary Achievement through Word Game: Meningkatkan Prestasi Kosakata Siswa melalui Permainan Kata - Hidayat, Nur (JEES (Journal of English Educators Society), 2016)
This paper is based on a study on students’ vocabulary of grade seven in junior high school using word game. This study is conducted based on the preliminary study which indicated that the students felt difficulties in learning English because of the lack of vocabulary.The subjects are 38 students who consist of 28 male, and 10 female students at seven grade of one of junior high schools in Gresik. The purpose of this study is to improve students’ vocabulary achievement through word game. The data is collected by interview, observation, questionnaires and test. The data is analyzed by using triangulation. The research design of this study is classroom action research which consist of four steps: planning, acting, observing and reflecting. The results of this study shows that word game can help students to memorize the vocabularies easier motivate students and make them more interested in learning vocabulary.